2019
DOI: 10.1523/eneuro.0334-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

CRF Mediates Stress-Induced Pathophysiological High-Frequency Oscillations in Traumatic Brain Injury

Abstract: It is not known why there is increased risk to have seizures with increased anxiety and stress after traumatic brain injury (TBI). Stressors cause the release of corticotropin-releasing factor (CRF) both from the hypothalamic pituitary adrenal (HPA) axis and from CNS neurons located in the central amygdala and GABAergic interneurons. We have previously shown that CRF signaling is plastic, becoming excitatory instead of inhibitory after the kindling model of epilepsy. Here, using Sprague Dawley rats we have fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The expression of CRF is increased in the amygdala following brain injury ( Narla et al, 2019 ; Tapp et al, 2019 ) and blockade of CRFR1 receptor 1 within the HPA axis attenuates post-traumatic stress and anxiety-like behaviors ( Kosari-Nasab et al, 2019 ). The activity of CRF in extrahypothalamic regions contributes to depression, anxiety, and fear-related behaviors ( Binder and Nemeroff, 2009 ; Sanford et al, 2017 ; Paretkar and Dimitrov, 2018 ).…”
Section: An Integrated Approach To Post-traumatic Affective Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CRF is increased in the amygdala following brain injury ( Narla et al, 2019 ; Tapp et al, 2019 ) and blockade of CRFR1 receptor 1 within the HPA axis attenuates post-traumatic stress and anxiety-like behaviors ( Kosari-Nasab et al, 2019 ). The activity of CRF in extrahypothalamic regions contributes to depression, anxiety, and fear-related behaviors ( Binder and Nemeroff, 2009 ; Sanford et al, 2017 ; Paretkar and Dimitrov, 2018 ).…”
Section: An Integrated Approach To Post-traumatic Affective Behaviorsmentioning
confidence: 99%
“…The CeA contains CRF-positive neurons ( Rodaros et al, 2007 ), whereas the BLA contains numerous CRF receptor-positive projection neurons ( Roozendaal et al, 2002 ). Increased CRF in the BLA can impair memory consolidation ( Narla et al, 2019 ), whereas increased CRF in the nucleus accumbens leads to depressive behaviors likely by modulating extracellular acetylcholine ( Chen et al, 2012 ); CRF receptor 1 antagonists exhibit antidepressant activity ( Overstreet and Griebel, 2004 ). Neurons within the CeA that express CRF have been investigated for their role in perpetuating anxiety behaviors following chronic stress ( Paretkar and Dimitrov, 2018 ; Hupalo et al, 2019 ) and promote fear learning by regulating acquisition recall ( Sanford et al, 2017 ).…”
Section: An Integrated Approach To Post-traumatic Affective Behaviorsmentioning
confidence: 99%
“…We found that a single dose of intraperitoneally injected ATM significantly reduced the 24 h average SRSs frequency by 41%, whereas a similar injection of the vehicle had no significant effect on this frequency. Interestingly, an anti-seizure effect of CRF 1 R antagonists was recently found also in EEG recordings from amygdala of rats subjected to traumatic brain injury, another type of insult causing TLE (Narla et al, 2019).…”
Section: Translational Implicationsmentioning
confidence: 79%
“…Basic science and understanding of molecular mechanisms in this area are also lacking in pediatrics. While there are several studies that address pituitary dysfunction following TBI (151)(152)(153)(154)(155)(156)(157), these studies have only been done in adult rats. Greco et al, utilized an adolescent mild rTBI model to examine hypopituitarism following TBI.…”
Section: Hormonalmentioning
confidence: 99%